Formulation development and evaluation of Glibenclamide loaded Eudragit RLPO microparticles - Kumar, Balagani Pavan; Chandiran, Irisappan Sarath; Jayaveera, Korlakunta Narasimha (International Current Pharmaceutical Journal, 2013)
The objective of the present investigation was to formulate and evaluate microencapsulated Glibenclamide produced by the emulsion solvent evaporation method. Microparticles were prepared using Eudragit RLPO by emulsion solvent evaporation method and characterized for their micromeritic properties, encapsulation efficiency, particle size, drug loading, FTIR, DSC, SEM analysis. In vitro release studies were performed in phosphate buffer (pH 7.4). Stability studies were conducted as per ICH guidelines. The resulting microparticles obtained by solvent evaporation method were free flowing in nature. The mean particle size of microparticles ranges from 134.49 179.72 µm and encapsulation efficiency ranges from 92.30-98.32%. The infrared spectra and differential scanning calorimetry thermographs confirmed the stable character of Glibenclamide in the drug-loaded microparticles. Scanning electron microscopy revealed that the microparticles were spherical in nature. In vitro release studies revealed that the drug release was sustained up to 12 hrs. The release kinetics of Glibenclamide from optimized formulation followed zero-order and peppas mechanism. The mechanism of drug release from the microparticles was found to be non-Fickian type. Eudragit RLPO microparticles containing Glibenclamide could be prepared successfully by using an emulsion solvent evaporation technique, which will not only sustain the release of drug but also manage complicacy of the diabetes in a better manner. DOI: http://dx.doi.org/10.3329/icpj.v2i12.17016 International Current Pharmaceutical Journal, November 2013, 2(12): 196-201